Medicinal plants: knowledge transmission in families of ecological farmers in souther Rio Grande do Sul - Ceolin, Teila; Heck, Rita Maria; Barbieri, Rosa Lía; Schwartz, Eda; Muniz, Rosani Manfrin; Pillon, Clenio Nailto (Revista da Escola de Enfermagem da USP, 2011)
The aim of this study was to investigate the process of knowledge transmission related to medicinal plants among family generations in the context of ecological farmers in Southern Rio Grande do Sul. This qualitative study was conducted with eight farming families, comprising 19 respondents living in the municipalities of Pelotas, Morro Redondo, Canguçu and Arroio do Padre. The interviews took place from January to May 2009. Data analysis was performed using the hermeneutic-dialectic method. The family was referred to as the main source in the transmission of knowledge about medicinal plants. Most subjects reported first completing treatment with medicinal plants, to then seek formal health service. The construction of knowledge related to medicinal plants by the families is predominantly oral, and takes place by the daily contact between its members and is shared with other members of the community to which they belong.